Atomic Quantum Galvanomagnetism Theory - Aragon, Pedro (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The establishment of galvanomagnetics properties inside the atom takes place here, giving sense, on axiomatic form, to a part of these properties. Some concepts are readjusted: quantum gravity is corrected and replaced by its real significance, and the atom pieces are identified through different quantum paths, among other things.